Telop, Affect, and Media Design: A Multimodal Analysis of Japanese TV Programs. (July 2017) - Sasamoto, Ryoko; O'Hagan, Minako; Doherty, Stephen
Japanese and other Asian TV producers have been deploying multi-colored, and highly visible, intra-lingual captions on TV programs to enhance their appeal and to influence their viewers' interpretations. The practice of adding these captions is far from innocent and is prone to abuse and overuse due to the lack of official guidelines and an evidence base. We conducted a multimodal analysis within the framework of relevance theory to provide an empirically supported insight into the way in which these captions, known as "telop" in Japan, form part of a production's deliberate and careful media design. Our findings suggest that telop are deployed in conjunction with other communicative resources that are deliberately used to influence viewers' interpretations, to enhance and make affective values in TV programs more explicit. The increasing use of diegetically integrated captions elsewhere further justifies the need for critical TV and new media research on telop.